Reevaluating the incidence of pervasive developmental disorders: Impact of elevated rates of detection through implementation of an integrated system of screening in Toyota, Japan - Kawamura, Yuichi; Takahashi, Osamu; Ishii, Takashi (Psychiatry and clinical neurosciences, 2008)
Aim:  Although recent epidemiological studies on the pervasive development disorders (PDD) appear to be reporting higher rates of incidence than previously believed, great variation in the reported figures suggests a need for review of the methodology involved. As such, a survey on the incidence of PDD was conducted and compared with data from a previous survey to examine the effects of screening and diagnostic methodology on incidence. Methods:  The incidence of pervasive developmental disorders was surveyed in all children (12 589) born between January 1994 and December 1996 in Toyota, Japan. Results:  Incidence was 1.81% and the ratio of boys to girls was 2.80. Definitive diagnoses were made between 13 months and 7 years 2 months, the average age at diagnosis being 3 years 4 months. Among the cases of PDD, children with normal or borderline intelligence amounted to 66.4%, mild mental retardation (MR) 17.5%, moderate MR 10.3% and severe MR 5.8%. Conclusion:  An approximately 11‐fold increase was noted in prevalence of PDD compared to a previous survey two decades ago, and two main factors were believed to account for this apparent sharp increase. First, inclusion of high‐functioning subjects detected during infancy, and second, higher rates of diagnosis resulting from an integrated process of screening.